REVIEW OF THE NATIONAL LEGAL SYSTEM ON THE MECHANISM OF RESOLVING CRIMINAL ACTS OF REGIONAL HEAD ELECTIONS BASED ON INTER-AGENCY AUTHORITY - Teguh Syuhada Lubis, Mhd (RADJA PUBLIKA, 2022)
An election crime can be formulated as any action/deed (active/passive) that violates the provisions in the stages of election administration and is threatened with criminal sanctions. Many people claim that at this time the election. This research uses normative legal research, with a research approach to legal systematics. Forms of normative legal research. The data of this study consisted of secondary data. Secondary data is data obtained from relevant literature studies in this study. Secondary data is